Death and short mourning – the real end of Young Poland - Gruchała, Wojciech (Requiem, 2025)
Franciszek Pik Mirandola died on June 3, 1930. His death was recorded in newspapers all over Poland, and the number of obituaries and posthumous memoirs was greater than the number of reviews of any of his artistic works. Initially, interest in Mirandola’s death was limited to family and the circle of friends, as evidenced by a quiet funeral without any signs of a national manifestation. However, the matter of his death revived the public debate not because of the topicality of Pik’s artistic program, but as a pretext to discuss the financial situation and the functions of artists in the newly created state order of the Second Polish Republic. The course of the funeral celebration determined by these facts allows us to diagnose the beginning of the 1930s as the end of the 19th century cultural idiom.